Human resource management merger between Limassol cooperative savings bank and peripheral cooperative credit society of Limassol - Georgiou, Marios (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
This diploma thesis explores the Human Resources Management during mergers and acquisitions (M&A), focusing on the banking sector and with a special analysis of the case of the recent merger of Cooperative Savings Bank of Limassol with Peripheral SPE of Limassol. The main pillars of the Human Resource Management (HRD) are outlined and the multiple roles that they are required to perform to ensure a healthy yet efficient work environment are mentioned. In-depth research is being carried out by distributing to the staff of the unified Bank of Analytical Questionnaires, which is designed to investigate the impact of M&A on the human resources of the two Banks and to capture the views of employees and to present the role Human Resource Management has played a successful role in managing key human resources issues and linking them to the strategic goals and processes of the merger.
Keywords: Human resources management; Mergers; Acquisitions; Banking sector